The development and validation of pre-driving assessment: attitude towards safe driving scale / Mohamad Ghazali Masuri - Masuri, Mohamad Ghazali (2020)
The number of fatality due to road traffic accident (RTA) has increased for the past few years. To date, on average 19.59 people were died every day due to RTA and the majority was among Malay young adult. Many reports have clearly stated that human factors contributed to up to 97% of RTA. This scenario creates concern from many agencies including health care professionals about the fundamental issue of this phenomena. There was a great public concern about assessment and intervention used by the enforcement body in Malaysia, where the outcome seems to be stagnant and hoping for the Ministry of Transport to look into this issue. Due to that, this study believes establishing proper outcome measure in identifying risk driving behaviour is essential. This study aims to develop a psychological assessment that will enable to assess Malay young adult attitude towards RTA. This study was involved sequential mix methodology approach. One-to-one semi-structured interview was conducted, involved three experts, two accident witness/victim and six victims. The verbatim transcripts were analysed by using six steps Interpretative Phenomenological Analysis. Six super-ordinate themes emerged that describes the expert views, victim and witnesses experiences towards RTA. Themes and sub-themes that emerged from the interview later translated into 46 attitudes based questionnaire namely; Attitude towards Safe Driving Scale (ASDS). The stem of the 46 questions were based on the themes and sub-theme. A total of 694 Malay young adult age ranged 18-36 years old had involved in the final study. The factor analysis was carried out to determine the validity and reliability of the assessment (Cronbach alpha .887). Each superordinate theme contains three to thirteen questions after undergoing factor loading analysis. The mean cut off for six domain and total score were also identified (D1: 45, D2: 36, D3: 32, D4: 20, D5: 12, D6: 9 and Total: 157). This assessment found to be adequate in providing the standard means of risky driving behaviour based on the cut off value. The ASDS also found to be valid and reliable in assessing the attitude status at an individual level. Face and content validity testing showed good coverage of the driving skills. Construct validity testing produced six important domains which show a high level of efficacy. As for the conclusion, the development of ASDS showed acceptable levels of reliability, construct validity, and criterion validity to recommend its use in assessing safe driving attitude among Malay young adult.